Gifted Students' Views About Teachers' Desired Characteristics - Tugba Hosgorur; Ali Gecer (ÜNİVERSİTEPARK Limited, 2012)
The aim of this study was to determine gifted students' teacher preferences. It was designed using the survey model, with both quantitative and qualitative approaches. Participants of the study were 296 gifted students attending Science and Art Centres in the Turkish cities. Data was gathered using the Preferred Instructor Characteristics Scale and adapted into Turkish by the researchers of this study. The quantitative data was analysed through descriptive statistics, t-test and Kruskal Wallis H tests, whilst the qualitative data was analysed through descriptive analysis technique. According to the findings of the study, gifted students consider personal-social characteristics to be more important than cognitive-intellectual characteristics. Preferences of characteristics that students want their teachers to possess do not differ in terms of gender, but they do differ in terms of age and grade. Students stated that they prefer teachers who are interested in them, make the class pleasant and understand them. On the contrary; students expressed that angry, uninterested and boring teachers were the characteristics of an ineffective teacher.